GAMBARAN PERENCANAAN KARIER SISWA SMP - Fera Hertiani Rosmana; Wikanengsih Wikanengsih; Maya Masyita Suherman (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2019)
Career planning is a process by which individuals can identify and take steps to achieve their career goals. Junior high school students in general have not been able to make good career plans, they do not have much information about careers, be it about secondary school or specialization in education and also work. The purpose of this study is to describe the description of junior high school student career planning. This research uses descriptive qualitative method. The subjects of this study were two students related to career planning at MTs Sirnamikin. The data collection techniques of this research were interviews and direct observation through school observations. The results showed that the potential and abilities of each student were different. Students must learn to consider and find a variety of information about the career they want. And so that all of this can materialize as they expect, therefore a good career planning is needed. Keywords: Career Planning, Middle School Students